Uji Aktivitas Fagositosis Makrofag Fraksi-fraksi dari Ekstrak Metanol Daun Sirih Merah (Piper crocatum Ruiz & Pav.) Secara In Vitro - YUSTINA SRI HARTINI; SUBAGUS WAHYUONO; SITARINA WIDYARINI; AGUSTINUS YUSWANTO (Fakultas Farmasi Universitas Pancasila, 2013)
Plants can be sources of immunomodulatory agents. Piper crocatum Ruiz & Pav. (red betel) leaves have been used to heal many diseases, especially to increase endurance. The aim of this research was to investigate the imunomodulatory effect of methanolic leaf extracts of Piper crocatum Ruiz & Pav. and its fractions by in vitro phagocytic macrophage activity test. The result showed that methanolic extract of Piper crocatum Ruiz & Pav. 75μg/mL could stimulate phagocytic macrophage activity equal to 100μg/mL product-X® that contained Echinacea extract. Separation of the extract by vacuum liquid chromatography using gradient solvent n-hexane - ethyl acetate yielded 5 fractions. The second fraction showed the highest activity. It contained alkaloid and terpenoid, while the extract also contained flavonoid and essential oil. Alkaloid and/or terpenoid could be the compound in the leaves of Piper crocatum Ruiz & Pav. that responsible increasing phagocytic macrophage activity.